TANGGUNG JAWAB HUKUM TERHADAP KERUSAKAN LINGKUNGAN DALAM KASUS LUMPUR LAPINDO MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2020 (UU CIPTAKER) - Yuliana Silvy Rosadi Zega; Fatma Ulfatun Najicha (Indonesian State Law Review, 2021)
The narrative about the establishment of Law No. 11 of 2020 has been realized through the ratification of The Job Creation Act on November 2, 2020 by President Jokowidodo. The establishment of The Job Creation Act aims to harmonize legislation that has been considered to hinder the investment and development climate. The number of related legislation causes hipper-regulation regulations so it may be ineffective. The existence of The Job Creation Act combines several instruments of law. One of them is the Law of Environmental Protection and Management (UUPPLH) which was originally regulated in Law No.32 of 2009. As for the substance of environmental issues in The Job Creation Act, some of them have been changed, revoked, and replaced with a new provisions, including provisions on the concept of responsibility in environmental law which known as strict liability. The author takes the description of the case of Lapindo Mud which is the case has not been completed until now as an example of the validity of strict liability principles for businesses whose activities cause environmental damage. This research is a normative juridical research with a statue and case approach. The data used is secondary data. The results showed that the concept of strict liability in The Job of Creation Act experienced a dis-orientation of meaning due to the removal of the phrase "without proof of the element of error". Under The Job of Creation Act, in the case of Lapindo Mud, the party subject to have strict liability is Lapindo Brantas Inc. and the government in this case are also responsible for the disaster, but do not assume to the strict liability.